Metode Hitungan Bagian Banci dalam Waris Islam: Analisis dan Praktik - Raja Ritonga (AL-HUKAMA: The Indonesian Journal of Islamic Family Law, 2021)
The concept of Islamic inheritance always proposes justice and the principle of benefit. The contradiction of age and the performance of body shaping does not become the standars in dividing inheritance. The differentiate between men and women often becomes chatter in controversy discussion. While, the hermaphrodit or khuntha sometimes are forgetten. In Islamic inheritance view, the hermaphrodit has a special portion and get portion, so this research’s aim to describe the counting methode of hermaphrodit portion in Islamic inheritence. The method is qualitative with the library research. Describing about the hermaphrodit al portion position and counting theirs portion as detail as possible. As the result in this research, the hermaphrodit are ddivided in to two parts; first, before they adult, they were called as khuntha mushkil al-raja’ (whom are still can not determine the gender and they still have hope), second, khuntha mushkil thula hayatihi (the hermaphrodit for their whole life and have no hope). Then, the hermaphrodit is counted for twice. Counting as the men and as the women. The hermaphrodit get a half of men inheritance and a half from women inheritance. Cause, the problem of both of counting of hermaphrodit portion times with the number two as a formula, until the value of the hermaphrodit inheritance is in the middle of men and women.